Robotic-assisted laparoscopic excision of a rare primary seminal vesicle leiomyoma - Kyle Carey; Karina Pique; Sammy A. Shihadeh; Anwar A. Khan; Cian Cranfield; Farzad Esfahani; Brett Parra (Urology Case Reports)
A primary seminal vesicle leiomyoma (PSVL) is a rare male genitourinary tract tumor. No previous reports have utilized a robotic-assisted laparoscopic posterior approach (RALPA) for surgical management. A 76-year-old man was incidentally found to have a 5cm lobulated mass posterior to the bladder in an abdominal/pelvic computed tomography scan. Biopsy confirmed leiomyoma. RALPA was utilized to excise the mass without complications. PSVLs are benign tumors with obstructive and minimal metastatic potential. Robotic-assisted surgery provides high fidelity, low risk, and an accelerated postoperative course compared to open surgery. The RALPA should be considered when surgical excision of PSVLs is required.